SUMBER DAYA ALAM, OTONOMI DAERAH DAN PERIMBANGAN KEUNGAN PUSAT-DAERAH - M. Zahrin Piliang (At-Tanmiyah Jurnal Ekonomi dan Bisnis Islam, 2022)
Since the nationalization of Dutch plantation companies due to Law no. 86 of 1958 indigenous peoples in Deli and the East Sumatra Region have generally lost their customary rights. The 1945 Constitution as a result of the amendment changed Article 18 of the 1945 Constitution into Article. 18B paragraph (2). Changes to this article resulted in the recognition of indigenous peoples, not accompanied by recognition of the position of the area inhabited by indigenous peoples. In other words, the position of indigenous peoples is no longer recognized, especially in the management of natural resources, , so that indigenous peoples do not have any share in state companies operating on their customary lands. In relation to the no longer recognized ownership of customary rights of indigenous peoples, the government has taken steps to use central-regional financial sharing instruments through the transfer mechanism of Balancing Funds, Special Autonomy Funds, and Adjustment Funds. The Balancing Fund consists of the General Allocation Fund (DAU), the Special Allocation Fund (DAK), and the Revenue Sharing Fund (DBH). Against this fact, the government of North Sumatra should fight for a minimum share of 30 percent in the two state-owned companies